Family-directed approach to brain injury (FAB) model: a preliminary framework to guide family-directed intervention for individuals with brain injury. Issue 7 (27th March 2019) - Fisher, Alinka; Bellon, Michelle; Lawn, Sharon; Lennon, Sheila; Sohlberg, McKay
Abstract: Purpose: This article proposes a theoretical framework to help professionals include family as active members in brain injury rehabilitation. A trend towards greater family involvement has lead to the development of family-collaboration models. However, current models appear to focus on information sharing rather than increasing the capability of family members. This article introduces a family-directed approach to brain injury model, which provides a theoretical framework for supporting family as facilitators of change. Methods: Family-collaboration models and literature regarding family experiences following brain injury and support needs are reviewed to identify the driving forces behind family engagement in rehabilitation, including effective professional–family relationships, and important factors in the delivery of education underpinned by evidence-based practices. Results: The family-directed approach to brain injury model is based on principles of hope, family expertise, education/skill building, and family-directed intervention. Conclusions: The family-directed approach to brain injury model provides a theoretical framework for educating and training family members as facilitators in the management process: promoting competence rather than dependency on service systems. Guiding recommendations encourage professionals to reflect on the importance of their therapeutic relationships and their capacity to positively impact rehabilitation outcomes beyond the technical aspects of health care and treatment. Implications for Rehabilitation: Training family members as facilitators in the rehabilitation process is suggested to reduce dependency on the service system, address families' unmet support needs, and to optimize rehabilitation outcomes for individuals with brain injury. The family-directed approach to brain injury model is proposed to guide the increased involvement of family as active members in the rehabilitation team and to define potential active ingredients in this process.